21st century sustainable homes - Cleary, Mark. (Victoria, Australia : The Images Publishing Group Pty Ltd, 2011)
Another addition to the highly successful 21st Century series The latest in sustainable housing design trends from around the world, providing inspiration and practical ideas Features lush color photographs of visually spectacular and environmentally-friendly architecture Showcases detailed plans and descriptions of each house and its sustainable elements. Necessity is the mother of invention, and the global necessity of facing the challenges of Climate Change has unleashed the inventive powers of architects around the world, many of whom are tackling the problem in original and highly creative ways. And yet, as the projects contained in this volume attest, sustainable design doesn't necessarily preclude style and comfort, or even a little bit of luxury. Locations include Australia, New Zealand, US, UK, Ireland, Spain, Portugal, Brazil, Malaysia, Russia, France and India. With lush full-colour photography, detailed floor and site plans, and informative descriptions of each house's sustainable design elements, Sustainable Homes takes the reader on a round-the-world journey, traversing a range of climates, to see how today's architects are making the most of traditional and modern design principles and technologies to create more energy efficient houses.
100K house -- Aptos family retreat -- Arrowtown house -- Autonomous house -- Bahia house -- BC house -- Big dig house -- Boano-Lowenstein residence -- Bungalow @ 5 polo club -- Cedeira house -- Christie beach residence -- COb2(B-saver -- Courtyard house -- Dalkeith house -- DT house -- El Ray house -- English residence -- Gap house -- Hill end ecohouse -- House 205 -- House among the pines -- House in Matsubara -- House in the forest -- House reduction -- House Ulve -- Hover house 3 -- Kelly residence -- King residence -- Kyneton house -- La Casa verde -- Loch Derg -- Marcus beach house -- Margarido house -- Mt. Veeder residence -- Oppenheimer residence -- Palmyra house -- Pepper Drive house -- Rainbow house -- Ross Street house -- Schierle house -- Shelter house -- Skyline residence -- Solar active house -- Steigereiland 2.0 -- Tehama grasshopper -- Toten farmhouse -- Treehouse -- Volga house.s
Includes index.
Keywords: SUSTAINABLE ARCHITECTURE -- PICTORIAL WORKS; SUSTAINABLE DESIGN -- PICTORIAL WORKS; ARCHITECTURE, DOMESTIC -- PICTORIAL WORKS